The influence of mandatory adoption of IFRS in Argentina on value relevance of accounting information - Florencia Roca (Journal of Applied Economics, 2021)
This study investigates the effect of mandatory adoption of International Financial Reporting Standards (IFRS) on the value relevance of accounting information in Argentina, which originated via the regulation that required all public non-financial companies to change the accounting standards, for fiscal periods starting in January 2012. As with most value-relevance studies, this research employs the Ohlson Model to examine the empirical association between equity prices and two main accounting variables: Net Earnings (representing the Income Statement) and the Book Value of Equity (representing the Balance Sheet). Panel data for 40 companies over a period of 23 years, from quarterly financial reports published by the Buenos Aires Stock Exchange (BCBA), are examined. The reported results suggest that mandatory adoption of IFRS in Argentina does not improve the value relevance of any of the tested variables. On the contrary, after the switch in accounting standards, the accounting numbers present a weaker association with the stock price.
Keywords: 330; Value relevance; Argentina; IFRS; value investing; Ohlson model